(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the process of learning the Italian language, the main challenges encountered, and effective strategies for overcoming them. In particular, pronunciation difficulties, gender and number agreement, and verb conjugation are examined separately. In addition to theoretical analysis, elements of practical observation are presented. The article also provides information on modern pedagogical approaches and interactive methods that help address these challenges.